Proposed interior design of kompang and Rebana Gallery at Lot Pt 4146 & 4147 Persiaran Sultan Izuddin Shah, Lumut, 32200 Perak for industri Rebana Sayong Sdn. Bhd. / Nur Alia Che Mohd Amran - Che Mohd Amran, Nur Alia (2012)
The final project for the final year students in Interior Architecture is based on all the knowledge gained from all the past semesters from semester one till semester five. All the knowledge that has been learnt from these semester will be put to the test by self proposing a final project based on real life factors such as the project itself, the client, the site and the budget. The chosen project will then go through several analysis and design processes before finally confirming the final design. The project choosen must have general issues and design issues related to them in order for it to be a visible project. Among the things that has been found that the Industry Rebana Sayong Sdn. Bhd. has plan to open a new branch gallery to commercialize kompang and rebana to the public in the Perak and the visitors. These issues then will be solved by the designers design after analyzing all the details needed before starting the design process. This project is funded by the Pusat Kraf Warisan.